UJI AKTIVITAS EKSTRAK BIJI SELASIH (Ocimum basilicum L.) DENGAN BEBERAPA PELARUT SEBAGAI ANTIPIRETIK PADA MENCIT (Mus musculus) - Rahimah, Sitti; hendrarti, Wahyu; Ramlah, Sitti (Jurnal Ilmiah As-Syifaa, 2015)
Seeds basil (Ocimum basilicum L.) has been known to the publicand is widely used to treat a variety of diseases. One of its benefits as lowering fever but have not been proven scientifically. This study was to determine whether there is an antipyretic effecte basil seeds (Ocimum basilicum L.) and to determine the effectiveness of extracts of basil seeds by using some of the solvent is n-hexane, ethyl acetate and ethanol compared with paracetamol in mice (Mus musculus). This study was an experimental study using RAL. Experimental animals used were 15 mice, stages of research giving treatment af mice in each group who had fasted for 12 hours, measured rectal temperature (initial temperature), then injected with 1 ml peptone/tail subcutaneously. The data obtained were analyzed ANOVA followed BNJ test. Test antipyretic extract basil seeds (Ocimum basilicum) with some solvent, most effectively used as a solvent in the basil seeds that solvent ethyl acetate compared with solvent n-hexane and ethanol. The results oft his study showed that the extract of basil seeds antipyretic effect.